Horizon as a Symbolic Category in Contemporary Site-Specific Art - Kochetkova, Ekaterina S. (Actual Problems of Theory and History of Art, 2020)
This paper intends to investigate various practices in contemporary art that intervene inlandscape surroundings. These forms of art have a privilege of not just depicting or imagining natural phenomena, but using them directly as essential components of the work. Thus, in this essay the category of horizon is treated in a very “palpable” way, though metaphorical and poetical at the same time. The physical and symbolic presence and interpretation of horizon in the art of the last five decades constitute the subject of this survey. The artistic strategies reviewed here include artificial creation or accentuation of the horizon line, massive interventions in the surface of the Earth, mechanisms of visual perception and focusing attention,exploration of spatial as well as temporal aspects of the notion, and many more. The concept of the horizon is present in the works of Ian Hamilton Finlay, Antony Gormley, Michael Heizer, Nancy Holt, Maya Lin, Walterde Maria, Robert Morris, Charles Ross, Richard Serra, Robert Smithson, James Turrell, and other artists. By addressing this theme, they utilize a wide range of media to remind us that the horizon is a utopian expression of the eternal longing for the unreachable.